SOCIAL CAPITAL IN INDONESIA: LITERATURE REVIEW - Irwandi, Irwandi (Yayasan Nuraini Ibrahim Mandiri, 2024)
Social capital and human capital are two interconnected and mutually reinforcing concepts. Social capital refers to social networks, interpersonal relationships, social norms, and trust within a community, while human capital emphasizes knowledge, skills, education, experience, and individual attributes that enhance productivity and economic value. Recent research indicates that an increase in human capital, such as higher education, improved skills, and broader experiences, can enhance the development of social capital within communities. This is because individuals with high human capital are more likely to engage in social activities and build relationships with others. Strong social capital can also promote the development of human capital through cooperation, access to information, and extensive social networks. This is because social capital can facilitate the sharing of information, resources, and support. Therefore, social capital and human capital are two crucial concepts that should be considered in economic and social development efforts. By enhancing both of these concepts, we can create more productive, prosperous, and sustainable societies.